(untitled) (e-Journal of Linguistics, 2023)
The global enthusiasm for online games requires the game developer and publisher to provide various language translations. The players require to communicate and strategize well to win the match. The Quick Chat used by MLBB players to communicate and build strategy must be translated as appropriate to the context. This research investigated the translation techniques applied to the Quick Chat verb in MLBB. Translation techniques are important for transmitting the message from ST to TT. Since Quick Chat primarily consists of verbs, this research focuses on the translation of illocutionary verbs of Quick Chat in MLBB. This research applied qualitative methods. Directive and assertive are the two illocutionary verbs found in 30 randomly selected data. Furthermore, five translation techniques applied in the illocutionary verbs are the literal, transposition, amplification, modulation, and reduction technique. Additionally, this study also reveals that the transposition technique changes the type of illocutionary acts from directive to assertive. Therefore, the selection of translation techniques should be appropriate to preserve the message and purpose of the Quick Chat.